The Influence of Flyer Momentum on an Aluminium Plate's Response to Underwater Shock Loading. (April 2019) - He, X.; Rong, J. L.; Xiang, D. L.; Wei, H. Y.; Hu, C. H.; Wang, X.
ABSTRACT: An underwater shock loading experimental device is used to simulate underwater explosion shock waves. The aim of this study is to investigate the influence of flyer momentum on the response of an aluminium plate to this underwater shock loading experimental device. The simulation accuracy can be verified by comparing theoretical data with the simulation and experimental results. Through simulations, an aluminium plate's deformation and pressure specific impulse can be determined when flyers impact the piston at different velocities but at the same momentum. The aluminium plate's deformation and pressure specific impulse are constant when the flyers had constant momentum because both are directly proportional to the flyer momentum. The results have an important practical value for understanding and using this type of experimental device.